Clinical Pattern of Neonatal Infections - Islam, MN; Hannan, Abdul; Hossain, S Zahid; Rahman, Md. Habibur; Razzaque, SA (Bangladesh Journal of Medical Science, 2014)
<!--[if gte mso 9]> <![endif]--> Neonatal infection is an important cause of morbidity and mortality among infants. Clinical pattern of neonatal infection in the neonatal unit of Institute of Post Graduate Medicine & Research (IPGM&R), Dhaka has been reported. Out of total 2160 Neonatal admission from July 1991 to June 1993, 320 (14.8%) cases of neonatal infections were found. Septicemia was the commonest type found in 118 (5.5%) cases. Other infections included umbilical sepsis (14.7%), Skin infections (1.6%), Meningitis (1.2%). Tetanus neonatorum were not included. Out of 320 cases, 20 patients died (6.2%). Preterm low birth weight and birth asphyxia were the common risk factors. DOI: http://dx.doi.org/10.3329.bjms.v1i3.17909 <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->